2021
DOI: 10.3389/fnsys.2021.655886
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of Sensorimotor Beta Oscillations

Abstract: Beta oscillations have been predominantly observed in sensorimotor cortices and basal ganglia structures and they are thought to be involved in somatosensory processing and motor control. Although beta activity is a distinct feature of healthy and pathological sensorimotor processing, the role of this rhythm is still under debate. Here we review recent findings about the role of beta oscillations during experimental manipulations (i.e., drugs and brain stimulation) and their alteration in aging and pathology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
86
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 86 publications
16
86
0
1
Order By: Relevance
“…An increase in the synchronisation of the beta oscillations during the forward motor imagery might be associated with an integration mechanism between premotor, sensory and somatosensory (including vestibular) processes. This is coherent with studies, which reported that synchronisation in beta oscillations linked to conscious motor processing (real or imagined) engages neural cortical premotor 65 , sensorimotor 66 , 67 and somatosensory activity 68 . Similarities between real motor execution and motor imagery oscillations at pre-motor, sensorimotor and parieto-temporal beta levels suggest that such neural activity is efferent and linked to the organisation of the ongoing movement 69 .…”
Section: Discussionsupporting
confidence: 90%
“…An increase in the synchronisation of the beta oscillations during the forward motor imagery might be associated with an integration mechanism between premotor, sensory and somatosensory (including vestibular) processes. This is coherent with studies, which reported that synchronisation in beta oscillations linked to conscious motor processing (real or imagined) engages neural cortical premotor 65 , sensorimotor 66 , 67 and somatosensory activity 68 . Similarities between real motor execution and motor imagery oscillations at pre-motor, sensorimotor and parieto-temporal beta levels suggest that such neural activity is efferent and linked to the organisation of the ongoing movement 69 .…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with prior studies, we found prominent beta band frequencies at rest in cortex, along with large and sustained beta desynchronizations during voluntary movements [47]. Resting beta power was also observed in STN, although it was considerably smaller in power and present less consistently (Figure 2).…”
Section: Beta Desynchronization Is Greater In Sensorimotor Cortex Tha...supporting
confidence: 91%
“…Movement-related beta oscillatory event-related desynchronization (ERD) and synchronization (ERS) have been characterized to a great extent in both healthy and clinical populations ( Kilavik et al, 2013 ; Little and Brown, 2014 ; Cao and Hu, 2016 ; Barone and Rossiter, 2021 ). On the other hand, the current knowledge on the functional significance of gamma ERS is more limited and mostly stems from a small number of studies, some with ECoG and intracranial recording in small samples of patients with various neurological problems ( Crone et al, 1998 ; Pfurtscheller et al, 2003 ; Androulidakis et al, 2007 ; Miller et al, 2007 ; Ball et al, 2008 ; Brücke et al, 2008 , 2012 ; Cheyne et al, 2008 ; Tan et al, 2013a , b , 2016 ; Flint et al, 2014 ; Miocinovic et al, 2015 ; Rowland et al, 2015 ; Gunduz et al, 2016 ; Ryun et al, 2017 ; Lofredi et al, 2018 ; Jiang et al, 2020 ), and a very few others with EEG or MEG in healthy subjects ( Muthukumaraswamy, 2010 ; Gaetz et al, 2013 ; Amo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%